The Mental Health of Caregivers and Their Patients With Dementia During the COVID-19 Pandemic: A Systematic Review - Carbone, Elvira Anna; de Filippis, Renato; Roberti, Roberta; Rania, Marianna; Destefano, Laura; Russo, Emilio; De Sarro, Giovambattista; Segura-Garcia, Cristina; De Fazio, Pasquale (Frontiers in Psychology, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is a worldwide public health concern. It continues to spread rapidly throughout the world causing multiple physical and psychological consequences in the population. Especially, people affected by severe psychiatric or neurological diseases are highly susceptible to serious health complications not only due to the direct effect of the infection but also to the indirect effect of COVID-19 following social distancing during lockdowns and its general social consequences. Indeed, lockdown and difficulties in using the care services produced psychological consequences in caregivers such as depression, anxiety, and worsening of the quality of life which in turn affected the ability to manage patients. Our aim was to systematically review the psychological consequences of the COVID-19 lockdown in caregivers of patients with cognitive impairment and dementia and the impact on the health of their patients. Methods: A systematic literature search was conducted by searching in MEDLINE/PubMed, Scopus, and Web of Science by two independent researchers following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines. Data extraction and quality assessment were also performed. Papers were screened for eligibility by abstract and then those which met inclusion criteria were included in this review. Results: The initial search returned 410 records. After the abstract screening and the inclusion/exclusion criteria were applied, 315 were excluded because they were irrelevant, 30 because they were reviews, meta-analyses, letters to editors, editorials, guidelines, or case reports, and 10 because they were duplicates. Then, 38 out of 55 abstracts/full-text articles were excluded because they did not simultaneously assess mental health of patients and caregivers. In the end, 17 papers were deemed eligible and included in the present review. Conclusion: Based on current literature, the COVID-19 pandemic and the ensuing lockdown caused severe psychological consequences for caregivers of patients with dementia, worsening their mental health, and increasing the psychological and physical burden, independently from the severity of the disease of their relatives, which resulted also independently globally worsened.